Evaluation of Mediating Role of Spiritual Intelligence in the Relationship between Social Capital and Psychological Capital of Graduate Students - Manijeh Shamsi; Naser Nastiezaie (Zanjan University of Medical Sciences and Health Services, 2019)
Background and Objective: Spiritual intelligence, social capital, and psychological capital are approaches that help the individual to coordinate with the environment, health and performance improvement. This study aimed to evaluate the role of spiritual intelligence in the relationship between social capital and psychological capital of postgraduate students of the University of Sistan and Baluchestan, Zahedan, Iran in the academic year of 2018-2019. Materials and Methods: This was an applied research in terms of goal and an analytical and correlational study in terms of methodology. In total, 341 postgraduate students were selected using proportionate stratified random sampling and according to the Cochran sampling formula. Data were collected employing spiritual intelligence questionnaire (King), social capital (Gaiani) and psychological capital inventory (Luthans et al.). Data analysis was performed in SPSS version 16 and LISREL using Pearson's correlation coefficient and the structural equation model. Results: In this study, the mean age of the students was 27.42±3.79 years. In addition, the mean social capital was 52.68±11.24 (out of 90), the psychological capital was 88.77±12.79 (out of 120), and the spiritual intelligence was 63.61±11.87 (out of 92). According to the results, the coefficient value of correlation of social capital with psychological capital (r=0.335, P<0.01), social capital with spiritual intelligence (r=0.359, P<0.01), and spiritual intelligence with psychological capital (r=0.585, P<0.01) was positive and significant. Furthermore, the direct effect of social capital on psychological capital (β=0.12, t=2.11), the direct impact of social capital on spiritual intelligence (β=0.42, t=6.78), and direct effect of spiritual intelligence on psychological capital (β=0.64, t=9.25) were positive and significant. The indirect effect of social capital on psychological capital was also significant and positive with the mediating role of spiritual intelligence (β=0.268). Conclusion: According to the results of the study, spiritual intelligence and social capital were positively correlated with the psychological capital of students. Therefore, the psychological capital of students could be improved by focusing on the growth of spiritual intelligence and social support.